Characteristics of changes in the functional status of the brain before and after 1,000 m all-out paddling for different levels of dragon boat athletes - Wu, Qianqian; Jiang, Hongke; Shao, Changzhuan; Zhang, Yan; Zhou, Wu; Cao, Yingying; Song, Jing; Shi, Bing; Chi, Aiping; Wang, Chao (Frontiers in Psychology, 2023)
Our purpose is to explore the changing characteristics of brain function of dragon boat athletes at different levels before and after exercise by monitoring the changes of EEG power spectrum and microstate of athletes before and after rowing. Twenty-four expert dragon boat athletes and twenty-five novice dragon boat athletes were selected as test subjects to perform the 1000m all-out paddling exercise on a dragon boat dynamometer. Their resting EEG data was collected pre- and post-exercise, and the EEG data was pre-processed and then analyzed using power spectrum and microstate based on Matlab software. Post-Exercise, the Heart Rate peak (HR peak), Percentage of Heart Rate max (HR max), Rating of Perceived Exertion (RPE) and Exercise duration of the novice group were significantly higher than expert group (P < 0.01). Pre-exercise, the power spectral density values in the δ, α1, α2, and β1 bands were significantly higher in the expert group compared to the novice group (P < 0.05). Post-exercise, the power spectral density values in the δ, θ, and α1 bands were significantly lower in the expert group compared to the novice group (P < 0.05), the power spectral density values of α2, β1 and β2 bands were significantly higher (P < 0.05). The results of microstate analysis showed that the duration and contribution of microstate class D were significantly higher in the pre-exercise expert group compared to the novice group (P < 0.05), the transition probabilities of A→D, C→D, and D→A were significantly higher (P < 0.05). Post-exercise, the duration and contribution of microstate class C in the expert group decreased significantly compared to the novice group (P < 0.05), the occurrence of microstate classes A and D were significantly higher (P < 0.05), the transition probability of A→B was significantly higher (P < 0.05), and the transition probabilities of C→D and D→C were significantly lower (P < 0.05). The functional brain state of dragon boat athletes was characterized by expert athletes with closer synaptic connections of brain neurons and higher activation of the dorsal attention network in the resting state pre-exercise.